A dimensão orante da celebração dominical da Palavra de Deus - Fernandes, Veronice (2021)
In Brazil, about 70% of communities gather on Sunday to celebrate the mysteries of faith around the Word of God. It is pertinent to reflect on the prayerful dimension of the Celebration of the Word of God, precisely because it is a celebratory practice of communities that are located on the outskirts of cities or in the hinterlands and inland beyond. These celebrations can be a space to nourish spirituality, mysticism, dialogue with God, rights of all the baptized, especially the poorest, deprived of so many things. In our research, we use the method that looks, knows, apprehends reality, that is, liturgical practice. It reflects on this practice in the light of Tradition and elaborates criteria for this same practice, that is, basically the see - judge - act method. First, we present data from the praying experience of participants in the Sunday Celebrations of the Word of God, obtained through a questionnaire that was answered by members of the Parish N.S. das Graças, located in Osasco-SP. Then, we developed a theoretical tool, with notions about liturgical prayer, prayer in general and the Sunday celebration of the Word of God. The reality data, read in the light of theoretical instruments, makes us realize that between current practice and Tradition there are converging and diverging points. We were able to see that in the celebrations of the Word of the communities of Osasco there is no lack of a prayerful dimension, even if the interviewees do not always feel and recognize it, but there are also difficulties that prevent these celebrations from being always praying. Lastly, we present suggestions for holding Sunday celebrations of the Word that are actually as prayerful as by their nature they should be